Interaction between IL13 genotype and environmental factors in the risk for allergic rhinitis in Korean children - Kim, Woo Kyung; Kwon, Ji-Won; Seo, Ju-Hee; Kim, Hyung Young; Yu, Jinho; Kim, Byoung-Ju; Kim, Hyo-Bin; Lee, So Yeon; Kim, Kyung Won; Kang, Mi-Jin; Shin, Yee-Jin; Hong, Soo-Jong (Journal of allergy and clinical immunology, 2012)
The prevalence of allergic rhinitis (AR) is increasing worldwide. Allergic diseases develop in susceptible subjects when they are exposed to specific environmental factors. We analyzed changes in the prevalence of AR and identified genetic and environmental factors in early childhood that affect risk. We used the International Study of Asthma and Allergies in Childhood questionnaire to collect data on AR, allergies, and environmental exposures from 4554 elementary school students from 5 areas of Seoul, Korea, in 2008. We also obtained DNA from 1050 subjects from 1 area of Seoul for genotype analysis of IL13. We identified genetic and environmental factors during infancy and early childhood that increased the risk for current AR (resulting in a diagnosis of AR and AR symptoms in the past 12 months) in elementary school–aged children. These included allergic disease in parents and antibiotic use in infants, allergic disease in parents and exposure of infants to mold, and allergic disease in parents and moving an infant to a newly built house. The risk of current AR also increased in subjects with GA or AA at nucleotide 2044 in IL13 who had been exposed to mold in the home during infancy (adjusted odds ratio, 3.27; 95% CI, 1.75-6.11) compared with subjects who had GG at this position and had not been exposed to mold (adjusted odds ratio, 3.27; 95% CI, 1.75-6.11). The prevalence of AR is increasing in Korean children. Children with a family history of allergic disease and exposure to specific environmental risk factors during infancy are more likely to have AR. Children with GA or AA at IL13(+2044) are at increased risk for AR when exposed to mold in the home during the first year of life.